Adopting and measuring customer service quality in Islamic banks: a case study - Shafie, Shahril; Wan Azmi, Wan Nursofiza; Haron, Sudin (Universiti Sains Islam Malaysia, 2004)
This study measures the perceptions of Islamic bank's retail customers in Malaysia using CARTER a new model to measure service quality.The findings of this study show significant validity for all CARTER's 35 items and six dimensions in terms of their importance in both weights and percentage.Amongst all six dimensions included in the model, the compliance dimension was reported to be most important by BIMB's customers and a strong link between service quality and customer satisfactions does exist.Thus, this study shows the importance for Islamic banks to place cultural difference in front when adopting service quality.